Efecto de varias fuentes fosfatadas colocadas a lado de la semilla sobre el rendimiento y rentabilidad del cultivo de maíz - Alcívar Holguín, Rudy Anderson (2019)
The research was carried out during the rainy season of 2019, in the towns of Casical and La Pitahaya of the Tosagua canton, Manabí, Ecuador. The aim of the research was to evaluate the effect of several phosphate sources placed next to the seed on the yield and profitability of the corn crop. The treatments evaluated were the fertilizers MESZ, Fertimaíz, Ecomaíz, Yaramilla complex and 10-30-10 placed next to the seed, and 10-30-10 placed in a band. In addition, a control treatment with phosphorus omission. The experimental design used was randomized complete blocks with seven treatments, three repetitions and 21 experimental units. The main variables recorded were performance and net economic benefit. The results showed significant differences (p <0.05) for performance between phosphate fertilization treatments and control treatment without P, in both locations evaluated. However, no differences were found between the phosphate fertilizers tested, which indicates that regardless of the sources and the form of application, phosphorus is a key element in increasing corn yield. The greater agronomic efficiency of P was achieved by complex fertilizers in relation to NPK-based classics. Finally, the greatest increase in yield and net economic benefit was achieved by the fertilizer fertilizer in both locations evaluated.